Penyuluhan dengan Metode Ceramah dan Diskusi Bersama Tentang Pencegahan Stunting Melalui Peran Orang Tua di Posyandu Dusun Curahwaru Desa Gambirono - Aulia, Anisa Nurina; Maulana, Dikdo Ainun; Shaffani, Yuninda Salva; Brahmantiyo, Ibrahim Nadhif; Firmansyah, Brian Arel (P3M Politeknik Negeri Jember, 2024)
Stunting is a condition where a person experiences chronic nutritional problems that arise as a result of a condition of malnutrition that lasts for quite a long time. One of the problems with knowledge about stunting prevention is through the role of parents. One way to increase knowledge is through health promotion, namely by providing education about stunting. The aim of this counseling is to increase parents' knowledge regarding stunting so that parents know how to prevent and overcome the problem of stunting. The method used is the outreach activity for parents of toddlers and pregnant mothers who carry out at Posyandu Mangga 110 Bangsalsari sub-district regarding the importance of monitoring children's growth and development by regularly checking them at the posyandu to see whether there is a risk of stunting in toddlers. Posyandu activities were carried out on March 10 2024 at Posyandu Mangga 110 Bangsalsari District. The results of this activity are increased knowledge and insight of parents about the importance of the role of parents in providing good nutrition as well as visits to posyandu to measure the height and weight of toddlers so they can monitor their children's growth and find out what signs and symptoms of stunting occur in toddlers and how to prevent it.